PERAN PEMERINTAH KABUPATEN WONOGIRI DALAM MENGATASI KEMISKINAN DI KECAMATAN KISMANTORO PERIODE 2011-2014 - Zerin Amorita; lusia astrika; Sulistyowati . (Journal of Politic and Government Studies, 2016)
Kismantoro sub-district is a district that has of high rates poverty inWonogiri as many as 2671 of Poor Households ( RTM ). The causative factorshigh rates of poverty in the district Kismantoro are a natural condition,productivity, and low-income communities. The aim of the research was todetermine how the government's role in solving poverty Wonogiri Regency inDistrict Kismantoro period 2011-2014, as well as to identify obstacle factors theimplementation of the Family Hope Program (PKH) in District Kismantoro.The research used a qualitative descriptive method to describe thecondition of an object of research by using the theory of the government role andthe poverty cycle theory as research guidelines.The result showed a decrease in the number of RTSM/KSM and increasedcommitment to the community in education and health. A database error,inadequate human resources companion, lack of capital for pioneering KUBE,and the low level of creativity and innovation of the PKH participant are theobstacle factors in the implementation of the CCT.The advice given to improving the quality of poverty countermeasuresprogram are the need for special program from the regional government shouldconduct an evaluation so the program could be running effectively and efficiently,as well as increased the motivation of the PKH participants to be able to take theadvantage of assistance.